Challenges of artificial intelligence on the learning process in higher education - Nicoleta Sîrghi; Mirela-Catrinel Voicu; Gratiela Georgiana Noja; Oana-Ramona Socoliuc (Amfiteatru Economic, 2024)
Artificial intelligence (AI) has expanded to unprecedented proportions in recent decades, penetrating vast areas, including education. The debates on the usefulness of incorporating AI into university education, with its subsequent opportunities and challenges, have captured the attention of the current research agenda. The fruitful exploitation of the AI advantages at the level of Romanian higher education is highly dependent on the specific set of knowledge, competences and abilities, even the capacity of the system to adapt to such a dynamic environment. Consequently, the objective of our research is to identify the skills necessary for the specific digital learning environment of Romanian higher education to encourage students as beneficiaries of the educational act to adopt AI technologies. Thus, our methodology consists of structural equation modelling applied to an original data set collected on the basis of a questionnaire addressed to undergraduate students from higher economic education. Results emphasise that the intention to adopt applications using AI among students directly depend on constructs such as perceived usefulness, attitude towards these technologies, perceived hedonic value, expected performance, or degree of compatibility, while the interactivity of the applications also has an important but indirect influence.
Keywords: D8; O33; I23; C15; J24; 330; artificial intelligence; higher education; learning outcomes; digital skills; structural equation modelling